2003
DOI: 10.1093/ps/82.3.408
|View full text |Cite
|
Sign up to set email alerts
|

Effects of L-carnitine on growth performance, carcass composition, and metabolism of lipids in male broilers

Abstract: We studied the effects of L-carnitine on growth performance, carcass composition, and lipid metabolism in male broilers. Six hundred male commercial broilers were allotted to five groups, each of which included three replicates (40 birds per replicate). The groups received the same basal diet supplemented with 0, 25, 50, 75, or 100 mg/kg L-carnitine, respectively. The feeding trial showed that L-carnitine had no significant effect on daily gain or feed conversion. Supplementation with L-carnitine (above 25 mg/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

22
133
2
2

Year Published

2005
2005
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 127 publications
(159 citation statements)
references
References 13 publications
22
133
2
2
Order By: Relevance
“…This finding is in agreement with other research (Curdak et al, 2007;Lien and Horng, 2001;Xu et al, 2003;Kheiri et al, 2011) which reports that L-carnitine supplementation did not have an effect on the growth performance of broiler chicks. Nevertheless, the results of Parsaeimehr et al (2012) showed that using Lcarnitine (300 ppm) in diets which contained 5 % animal fat improved body weight gain and feed conversion ratio of broiler chicks in a comparison to diets containing 5 % soybean oil.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…This finding is in agreement with other research (Curdak et al, 2007;Lien and Horng, 2001;Xu et al, 2003;Kheiri et al, 2011) which reports that L-carnitine supplementation did not have an effect on the growth performance of broiler chicks. Nevertheless, the results of Parsaeimehr et al (2012) showed that using Lcarnitine (300 ppm) in diets which contained 5 % animal fat improved body weight gain and feed conversion ratio of broiler chicks in a comparison to diets containing 5 % soybean oil.…”
Section: Discussionsupporting
confidence: 93%
“…Several studies have been done to study the effect of L-carnitine on broiler chickens, but the results obtained are not in agreement. Some studies have shown that supplemental L-carnitine improved body weight gain and reduced the abdominal fat content of broilers (Rabie et al, 1997a, b) but other research (Xu et al, 2003;Leibetseder, 1995) observed no effects of L-carnitine on chicken growth performance. Because of the conflicting reports about the effects of Lcarnitine supplementation, it seems that the dietary composition such as oil source (fatty acids) may have an effect on the bird's growth performance.…”
Section: Introductionmentioning
confidence: 99%
“…However, Eder (2000) reported higher concentrations of cholesterol in plasma and some researchers observed reduced concentrations of serum cholesterol and triglyceride levels in rabbits (Bell et al, 1987) and rats (Mondola et al, 1992). Xu et al (2003) concluded that supplementation of 50, 75 or 100 mg L-carnitine/kg decreased the activity of lipoprotein lipase, thereby leading to a higher concentration of fatty acid in the serum by accelerating hydrolysis of triglycerides to glycerol and fatty acids, while reducing the serum concentration of triglycerides. Table 4 Effects of carnitine and humate supplementation on blood serum parameters of laying quails Schuhmacher et al (1993) observed that carnitine seemed effective in improving body weight gain and feed conversion ratio, especially in groups with diets marginally deficient in lysine and methionine plus cystine.…”
Section: Resultsmentioning
confidence: 99%
“…Soy protein diets in rodents suppressed the expression of hepatic lipogenic enzymes and lowered the expression of SREBP-1, FAS and ME in the liver (Iritani et al, 1996;Ascencio et al, 2004). The liver in birds is known to be the main site of fatty acid synthesis (Xu et al, 2003), and liver fatty acid metabolism has been recognized as the main source of variation in fat deposition and blood TG concentrations in poultry (O'Hea and Leveille, 1969). Previous studies have shown that SREBP-1c can directly stimulate the transcription of genes encoding ACC, the rate-limiting enzyme in fatty acid synthesis (Stoeckman and Towle, 2002;Yin et al, 2002), making it a good candidate for a common regulator of the lipogenic genes expressed in avian liver.…”
Section: Discussionmentioning
confidence: 99%
“…The liver is known to be the primary site of fatty acid synthesis in birds (Xu et al, 2003), and most of the body's endogenous lipids are hepatic in origin (O'Hea and Leveille, 1969). As in mammals, enzymes in the avian liver control sterol and lipid metabolism, and the levels of mRNA expression of lipogenic genes have been reported to parallel changes in enzyme activity, such as fatty acid synthase (FAS; Back et al, 1986).…”
Section: Introductionmentioning
confidence: 99%